Implementing Deep Learning to Enhance Students' Literacy and Numeracy Skills - Rida Hartatik Rida; Sumi Herni; Nur Cholis; Ichsan Anshory AM; Arina Restian (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Literacy and numeracy skills are essential basic skills for student learning success, but achievement levels in Indonesia are still far from expectations. Deep learning methods are proposed as a modern solution that focuses on meaningful conceptual understanding, active student participation, and the development of critical, reflective, and creative thinking skills. By using approaches such as problem-based learning, project-based learning, and collaborative discussions supported by digital technology, deep learning can efficiently combine literacy and numeracy in real learning situations. The application of this approach not only serves to improve reading, comprehension, and numeracy skills in a practical way but also helps shape adaptable and independent characters, in line with the vision of the Merdeka Curriculum. It is hoped that applying deep learning in literacy and numeracy will produce a generation of students who are superior and ready to face the challenges of the 21st century comprehensively and sustainably.